Unregulated proliferation of primitive neoplastic progenitor cells in long-term polycythemia vera marrow cultures. - Cashman, J D; Eaves, C J; Eaves, A C (The Journal of Clinical Investigation, 1988)
Marrow cells from seven untreated patients with polycythemia vera (PV) were used to initiate standard single inoculum long-term marrow cultures. The numbers, erythropoietin independence, and cycling behavior of all detectable classes of erythroid, granulopoietic, and multilineage progenitors were then evaluated and the results obtained compared with preculture values. Time course studies showed that the long-term marrow culture system supports the continuous proliferation of primitive neoplastic progenitor cells from PV patients for many weeks. However, these progenitors fail to respond to signals from the adherent layer that return their counterparts in normal long-term marrow cultures to a quiescent state 5-7 d after each medium change. This abnormal cycling behavior of PV cells in the long-term culture system appears to mimic that operative in vivo, where primitive hemopoietic progenitors are also in a continuous state of turnover, in contrast to similar primitive progenitor compartments in normal individuals, which are quiescent. The long-term marrow culture system thus offers new possibilities for the further analysis of abnormal cellular and molecular mechanisms underlying clonal expansion at the stem cell level in PV. Images